2019
DOI: 10.1210/jc.2019-00350
|View full text |Cite
|
Sign up to set email alerts
|

Differential Levels of Regulatory T Cells and T-Helper-17 Cells in Women With Early and Advanced Endometriosis

Abstract: Context Regulatory T (Treg) cells and T-helper-17 (Th17) cells may be involved in endometriosis. Information on the pattern of change in the percentages of Treg and Th17 cells in the peripheral blood (PB) and peritoneal fluid (PF) of women with early and advanced endometriosis is unclear. Objective To investigate the pattern of change in the percentages of Treg and Th17 cells in the PB and PF of women with early and advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 49 publications
4
50
0
Order By: Relevance
“…Most studies suggest the proportion of Tregs is significantly increased in peritoneal fluid from women with endometriosis compared with control women (157,158,161). One study reported that the number of Tregs was increased in the peritoneal fluid and decreased in the peripheral blood, and another study found the number of Tregs was higher in peritoneal fluid than in peripheral blood, both indicating that active translocation of Tregs occurs from circulation to the local peritoneal cavity (158,162). However, some studies failed to find any difference in the proportion of Tregs in patients with endometriosis when compared with women without endometriosis (159).…”
Section: Endometriosismentioning
confidence: 99%
“…Most studies suggest the proportion of Tregs is significantly increased in peritoneal fluid from women with endometriosis compared with control women (157,158,161). One study reported that the number of Tregs was increased in the peritoneal fluid and decreased in the peripheral blood, and another study found the number of Tregs was higher in peritoneal fluid than in peripheral blood, both indicating that active translocation of Tregs occurs from circulation to the local peritoneal cavity (158,162). However, some studies failed to find any difference in the proportion of Tregs in patients with endometriosis when compared with women without endometriosis (159).…”
Section: Endometriosismentioning
confidence: 99%
“…Ectopic Foxp3 expression can phenotypically convert effector T cells to regulatory T cells [37]. A recent research found that endometriosis is related to changes in Treg and Th17 cells in the pelvis, leading to the survival and implantation of ectopic endometrial lesions [38]. The percentage of CD25 + FOXP3 + Treg cells is significantly increased in the peritoneal fluid of women with endometriosis [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, OE is an inflammatory disease, which involves multiple organs, including the ovary and the uterus 12 . The peripheral subsets of immune cells are also considered suitable for evaluating the inflammatory status of OE 13 , 14 . Therefore, the number of peripheral CD56+ NKG2D+ NK cells can be used as a preoperative biomarker in OE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, OE is often considered an inflammatory disease 12 . Notably, dysfunction of various lymphocyte subpopulations is pivotal for the pathogenesis of endometriosis 13 , 14 . For example, the imbalance of helper T cells (Th), B cells and Natural Killer (NK) cells, can lead to inflammation and further development of the ovarian lesions in OE 12 .…”
Section: Introductionmentioning
confidence: 99%